2011
DOI: 10.1039/c0dt01244k
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyl iron complexes—synthesis, structure and biology

Abstract: Nitrosyl complexes of iron are formed in living species in the presence of nitric oxide. They are considered a form in which NO can be stored and stabilized within a living cell. Upon entering a topic in bioinorganic chemistry the researcher faces a wide spectrum of issues concerning synthetic methods, the structure and chemical properties of the complex on the one hand, and its biological implications on the other. The aim of this review is to present the newest knowledge on nitrosyl iron complexes, summarizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 212 publications
(215 reference statements)
0
78
0
Order By: Relevance
“…These complexes contain one iron, two nitrosyl groups, and two other ligands, all binding to iron ((L) 2 Fe(NO) 2 ) (3)(4)(5). In cells, low molecular weight thiols and cysteine-containing proteins (RSH) constitute the majority of DNIC ligands (3)(4)(5). DNIC exhibit a unique EPR spectrum characterized by a principal g value of 2.03.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These complexes contain one iron, two nitrosyl groups, and two other ligands, all binding to iron ((L) 2 Fe(NO) 2 ) (3)(4)(5). In cells, low molecular weight thiols and cysteine-containing proteins (RSH) constitute the majority of DNIC ligands (3)(4)(5). DNIC exhibit a unique EPR spectrum characterized by a principal g value of 2.03.…”
mentioning
confidence: 99%
“…It has been reported that the most abundant cellular adduct of ⅐ NO is dinitrosyliron complexes (DNIC) 5 (2). These complexes contain one iron, two nitrosyl groups, and two other ligands, all binding to iron ((L) 2 Fe(NO) 2 ) (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrosyl complexes have been the object of strong and important studies because of their particular chemistry [18][19][20]. This radical manifests ubiquitous and chameleonic behavior that depends on its electronic count: it can act as a cation NO + , a neutral free radical NO or an anion NO -.…”
Section: No Complexmentioning
confidence: 99%
“…15 Although the majority of biological DNICs have S-donor ligands, such as cysteinate, DNICs ligated by other O/N-donor residues have also been observed. 5 Significant progress has been made in the identification of DNICs as the products of NO-mediated [Fe−S] cluster degradation, but it is not well understood what other product(s) may form during cluster degradation. Moreover, the effects that DNICs and other degradation products elicit once they are generated in cells also remain unknown.…”
Section: ■ Introductionmentioning
confidence: 99%